2021
DOI: 10.3390/molecules26175389
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin Color Stabilization by Host-Guest Complexation with p-Sulfonatocalix[n]arenes

Abstract: Flavylium-based compounds in their acidic and cationic form bring color to aqueous solutions, while under slightly acidic or neutral conditions they commonly bring discoloration. Selective host-guest complexation between water-soluble p-sulfonatocalix[n]arenes (SCn) macrocycles and the flavylium cationic species can increase the stability of the colored form, expanding its domain over the pH scale. The association constants between SCn and the cationic (acid) and neutral basic forms of flavylium-based compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The binding constants (K), obtained at pH 1, which are compiled in Table 1, span from 3.00 × 10 3 M −1 for the SC6 complex to 8.41 × 10 4 M −1 for the complex formed with SC8, being within the range of values previously reported for the complexation of other flavylium compounds with sulfonated calixarenes. 14,45 Regarding the affinity for the sulfonatocalixarenes, these results suggest that the SCn cavity size and/or the number of sulfonate groups are not the main factors controlling the selectivity, and aspects such as flexibility and conformational structure of the hosts might also have an important influence.…”
Section: Association Constants (K)mentioning
confidence: 95%
See 1 more Smart Citation
“…The binding constants (K), obtained at pH 1, which are compiled in Table 1, span from 3.00 × 10 3 M −1 for the SC6 complex to 8.41 × 10 4 M −1 for the complex formed with SC8, being within the range of values previously reported for the complexation of other flavylium compounds with sulfonated calixarenes. 14,45 Regarding the affinity for the sulfonatocalixarenes, these results suggest that the SCn cavity size and/or the number of sulfonate groups are not the main factors controlling the selectivity, and aspects such as flexibility and conformational structure of the hosts might also have an important influence.…”
Section: Association Constants (K)mentioning
confidence: 95%
“…Upward pK a shifts are frequently observed for sulfonated calixarene-based host−guest complexes, including flavylium cations, as a result of the selectivity of these receptors toward positively charged species. 45,48,49 3.4. BA Sensing by Host−Guest Systems.…”
Section: Thermodynamic Parameters (Pk a )mentioning
confidence: 99%
“…(5) it has a relatively rigid backbone structure, which facilitates the stability of supramolecular assemblies. In 2021, Mendoza's research group [39] constructed a complexation product of sulfonated calixarenes and anthocyanin cations by host-guest interaction and found that the product has higher modifiability and also the product is more stable under different pH conditions, thus constructing ALHS that can adapt to a wide range of pH changes.…”
Section: Artificial Light-harvesting System Based On Macrocyclic Cavi...mentioning
confidence: 99%
“…Calixarene is of wide interest due to several advantages: (1) it has a simple preparation process, can be prepared by direct sulfonation, and easy to obtain raw materials; (2) The sulfonic acid group has good water solubility, but is compatible with the hydrophobicity of macrocyclic molecules and the π–π stacking of benzene rings, thus enhancing the complexation of the host and guest; (3) it has good biocompatibility; (4) Sulfonate anion easily binds to organic cations to improve specific selectivity; (5) it has a relatively rigid backbone structure, which facilitates the stability of supramolecular assemblies. In 2021, Mendoza's research group [39] constructed a complexation product of sulfonated calixarenes and anthocyanin cations by host‐guest interaction and found that the product has higher modifiability and also the product is more stable under different pH conditions, thus constructing ALHS that can adapt to a wide range of pH changes.…”
Section: Artificial Light‐harvesting System Based On Supramolecular S...mentioning
confidence: 99%
“…[32][33][34] Water soluble macrocyclic arenes have the ability to recognize and assemble in water, which is of practical signicance for understanding and mimicking biological processes. [35][36][37][38] By introducing the water soluble groups into suitable positions on the macrocyclic arenes, water-soluble macrocyclics can be easily obtained. Water soluble carboxylatopillar[n]arenes [39][40][41][42] and psulfonatocalix[n]arenes [43][44][45] have gained maximum popularity for their easy preparation, p-electron rich hydrophobic cavity, ideal candidates for host-guest binding with cationic guests and application in fabricating responsive supramolecular systems and as nanovalves for trapping and releasing cargo molecules.…”
mentioning
confidence: 99%